THU0448 Secukinumab for The Treatment of Psoriatic Arthritis: Comparative Effectiveness Results versus Adalimumab Up To 48 Weeks Using A Matching-Adjusted Indirect Comparison. (15th July 2016) - Nash, P.; McInnes, I.B.; Mease, P.; Thom, H.; Cure, S.; Palaka, E.; Gandhi, K.; Mpofu, S.; Jugl, S.
Abstract : Background: Secukinumab (SEC) is approved for the treatment of active PsA in adults with inadequate response to DMARDs. The FUTURE 2 (F2) trial showed superiority of SEC 150 mg and 300 mg over placebo for the primary outcome of ACR20 response at week 24 and for multiple secondary outcomes, with efficacy sustained to week 52. The ADEPT trial compared adalimumab 40 mg (ADA) with placebo in biologic-naïve patients. In F2, patients could switch from placebo (from week 16); for both trials all had switched after week 24. In the absence of direct comparison or a continuous common placebo arm, matching-adjusted indirect comparison (MAIC) can assess relative efficacy. MAIC adjusts for differences in patient characteristics at baseline, reducing the effective sample size (ESS) for the therapy arm in one trial, but matching this with the population of the therapy arm from another trial, thus simulating head-to-head comparison. Objectives: To assess the relative efficacy of SEC 150 mg and 300 mg vs. ADA using F2 and the published ADEPT trial. Methods: Patient-level data from the SEC arms of the F2 trial (n=200 across SEC doses) were weighted to match patient baseline characteristics for the ADA arm of ADEPT (n=151). Logistic regression was used to determine weights for age, body weight, sex, race, methotrexate use, presence of psoriasis (≥3% body surface area), mean PASI score, dactylitis, enthesitis, mean HAQ-DI and previous biologic therapy. Weighted outcomes from F2 (ESS: n=36 for SEC 150 mg; n=38 for SEC 300 mg) were compared with data from ADEPT (both trials used non-responder imputation). Pairwise comparisons using relative risks (RRs) were performed and results are presented as RR (95% CI) and probability of response (95% CI) for ACR20, 50 and 70 at week 48. For PASI75 and 90, ADA week 48 results are compared with SEC week 52 data (the nearest data point). Results: In the MAIC, both SEC doses had higher mean ACR20, 50 and 70 responses than ADA, with statistical significance for SEC 150 mg (RR: 1.41 [1.14–1.76], p =0.002) and SEC 300 mg (RR: 1.31 [1.03–1.66], p =0.027) at ACR20 and for SEC 300 mg (RR: 1.41 [1.03–1.92], p =0.032) at ACR50. The ACR20, 50 and 70 response rates were 79.6% (72–88), 57.1% (47–67) and 32.4% (23–42) respectively for SEC 150 mg; 73.5% (64–83), 61.4% (51–71) and 42.9% (33–53) for SEC 300 mg; and 56.3% (48–64), 43.7% (36–52) and 29.8% (23–37) for ADA. Findings were consistent across sensitivity analyses which also showed significance for SEC 300 mg at ACR70. PASI 75 and 90 response rates were numerically better for SEC 300 mg: 71.1% (57–86) and 52.2% (36–68) than ADA: 58.0% (46–70) and 46.4% (35–58). SEC 150 mg rates were 51.2% (38–64) and 40.8% (28–54) respectively. Conclusions: When adjusted for patient baseline characteristics, SEC was associated with numerically higher response rates for joint and skin outcomes with statistically significantly higher responses vs. ADA for ACR endpoints at week 48. The next level of evidence will be a head-to-head to substantiate these findings. Disclosure of Interest: P. Nash Grant/research support from: Novartis, Consultant for: Novartis, I. McInnes Consultant for: Novartis, Janssen, Abbvie, Pfizer and UCB, P. Mease Grant/research support from: Corrona, Speakers bureau: Corrona, Merck and Novartis, H. Thom Consultant for: Novartis Pharma AG and for a short time in 2015 for Eli Lilly, S. Cure: None declared, E. Palaka Employee of: Novartis, K. Gandhi Shareholder of: Novartis, Employee of: Novartis, S. Mpofu Shareholder of: Novartis, Employee of: Novartis, S. Jugl Shareholder of: Novartis, Employee of: Novartis